Visual Outcome of Ocular Trauma - Humaira Fawad, Sana Nadeem, Muhammad Ayub (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the causes and visual outcome of ocular trauma threatening vision. Material and Methods: This study was conducted at the Department of Ophthalmology, Holy Family Hospital, Rawalpindi, from 1st November, 2011 to 30th September, 2012. Visually significant ocular trauma included all cases with any decrease in vision at presentation. A detailed history with complete ocular examination was undertaken and relevant investigations were done as necessary. Patients were treated medically or surgically as the case may be. Follow up ranged from 1 month to 10 months. Results: Our study found a male preponderance in ocular trauma patients, with a male to female ratio of 4.92:1.The commonest agents responsible being stones and wooden sticks, both constituting 10 (12%) cases each. Unilateral involvement occurred in 82 (98.8%) cases. Blunt trauma cases were the most frequent, pertaining to 47 (56.6%) cases. The anterior segment was predominantly involved with 55 (66.3%) cases. Complex patterns of trauma were observed. The post-operative best corrected visual outcome was statistically significant to the pre-operative visual acuity with 24 (28.9%) eyes attaining a visual acuity of 6/6 (p = 0.000). The greatest number of cases were managed conservatively with medical treatment i.e. 36 (43.4%), and the rest required surgeries. Conclusion: Ocular trauma is a great threat to vision. Early recognition of the severity, adequate evaluation, and appropriate management lead to a better visual outcome.